(3JaSjQ GdKYGdHis - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s
(3ChdgG (B:s
(3jHJOF HJaSjQ ShQI GdGYQGa s
(3BNQgG (B:s
( (3jfJgi HJaSjQ BNQ GdShQI GdJi bHd ShQI jhfS eHGTQ(B) (3QGLY GdeUMa dcJGHI GSegG s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B189s
(3cTa GdXfhf (B- (3GdLRA (B2 - (3U (B1488 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B444s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdJaSjQ hYdhe GdbQBfs